Subcutaneous calcification in the pectoralis major flap: a late complication of radiotherapy - Plzák, Jan; Kalitova, P; Urbanova, M; Betka, J (British journal of radiology, 2011)
Heterotopic calcification following radiotherapy is a very rare event. Here, we report a case of a patient who underwent surgical intervention including pectoralis major flap reconstruction for locally advanced pharyngolaryngeal squamous cell carcinoma with skin invasion. He was followed up post-operatively with adjuvant radiotherapy. 13 years after the treatment, suspect resistance in the myocutaneous flap region appeared and was diagnosed as a calcification. To date, the occurrence of subcutaneous calcification in the myocutaneous flap in the neck has not been described as a late complication of neck irradiation.
Keywords: Carcinoma, Squamous Cell; invazivní růst nádoru; Pectoralis Muscles; chirurgické laloky; nádory hlavy a krku; Calcinosis; lidé; Surgical Flaps; nádory kůže; adjuvantní radioterapie; prsní svaly; Head and Neck Neoplasms; Male; Aged; Skin Neoplasms; spinocelulární karcinom; Radiotherapy, Adjuvant; senioři; mužské pohlaví; Neoplasm Invasiveness; kalcinóza; Humans